Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Keywords: Japan; Russia; economic development; rural economies

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Nationalist Politics and the Double Movement: The Problem of Legitimacy in Neoliberal States - Blad, Cory (2013)
This paper argues that the contemporary efficacy of nationalist politics is a strategic response to neoliberal conditions of state legitimation. Using the double movement as a theoretical framework, I argue that neoliberalism alters the policy alternatives available to state actors by reducing the viability of economic protectionist initiatives once dominant in the embedded liberal era. This policy capacity reduction inhibits some of the key means for state legitimation (e.g., public spending, regulatory protectionism), which exacerbate the negative effects of capitalist liberalization. As national populations view the state as unwilling or unable to mitigate economic adversities or provide traditional socio-economic services, significant potential exists for a delegitimation of state actors and institutions. In response, neoliberal state actors have gravitated toward an increasingly cultural rhetoric of nationalism as a means to maintain popular legitimacy. This shift goes beyond simple political power struggles - in accordance with the double movement framework, systemic global capitalism requires legitimate state authority to ensure both local stability and sustained capital accumulation. Neoliberal ideology, however, discourages traditional means of state legitimation. A Polanyian examination of this ironic condition offers a structural explanation for the increased efficacy of nationalist politics; however, it also raises serious questions about the sustainability of this legitimation strategy.
Keywords: double movement; globalization; nationalism; neoliberalism; state legitimation

Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Keywords: embeddedness; rural entrepreneurships; social networks

Social Economy and the fight against Social Exclusion: Preliminary remarks with reference to the Greek welfare state - Adam, Sofia (1st International Conference in Political Economy, 2010)
Recent academic discourse and European social policies highlight the (potential) effectiveness of social economy practices as a means to address social exclusion especially for the more disadvantaged social groups. Apart from terminological debates on the aforementioned troubled concepts, fundamental questions needs to be examined: To what extent social economy practices flourish as a result of policy shifts towards further commercialization of public social services or to what extent do they emerge from bottom up collective survival strategies? This paper attempts to address this question with reference to the political economy of the Greek welfare state.
Keywords: Greece; economic sociology; embeddness; political economy; social economy; substantive approach; welfare state

Karl Polanyi et les monnaies modernes : un réexamen - Blanc, Jérôme (L'Harmattan, 2006)
Karl Polanyi a établi une célèbre distinction entre "all purpose money", caractéristiques des sociétés modernes, et "special purpose money", caractéristiques des sociétés anciennes. C'est la conception polanyienne des monnaies modernes qui est critiquée dans ce texte : non seulement elle conduit à considérer que les sociétés modernes ne connaissent pas de "special purpose money", mais en plus elle ne permet pas de renouveler la conception courante de la monnaie (sous-entendu moderne) qui en fait un moyen de paiement universel. ENG translation: Karl Polanyi has established a famous distinction between "all purpose money" characteristic of modern societies, and "special purpose money", characteristic of ancient societies. It is the Polish conception of modern currencies that is criticized in this text: not only does it lead to the view that modern societies do not know a "special purpose money", but also does not allow to renew the current conception of Currency (modern underlining) which makes it a universal means of payment.
Keywords: Monnaie moderne. Pratiques monétaires. Polanyi. Monnaies parallèles. Fongibilité. Cloisonnements.; boundaries; fungibility; modern money; monetary uses; parallel currencies

The Dark Side of Embeddeness: The Construction of Economic space and Prestige in Italy 1896-1907 - Polillo, Simone (Conference Papers -- American Sociological Association, 2006)
The creation of a national economic space is the necessary structural condition for the unfolding of the "self-protective" measures of society that Polanyi analyzed for the post-WWI period, and that he saw as more generally arising in response to free market policies. A national economic space is itself the product of specific institutional arrangements, in particular the state agencies that allow the state to centralize the monetary system in its own hands: in the modern period, these have been central banks. By analyzing a longitudinal sample of the minutes of the meetings of the governing body of the Bank of Italy in its crucial transitional period at the turn of the century (1896-1907), this paper attempts to trace the historical process by which the Italian economy came to be understood as a national space. It shows that the creation of an area of economic prestige measured by the technical success of the central bank and the strength of its relationship with the Treasury was a crucial achievement of the liberal state. ..PAT.-Unpublished Manuscript
Keywords: Italy; World War I; banking industry; central bank; embeddedness; manuscripts; monetary policy; money; saving and investment; self-protective measures; state

Retelling the Great Transformation - Steinberg, Marc (Conference Papers -- American Sociological Association, 2006)
In this paper I partly retell Polanyi's narrative of the industrial revolution found in his Great Transformation. I discuss how new labor laws consolidated in the 19th century created a legal structure of coerced contractual labor, that did not fit the ideals of free market economics. My retelling focuses on how capitalists in some industries relied on legal coercion of their workers as a means of discipline and labor process control. Through this retelling I demonstrate that Polanyi was still beholden to neo-classical economics in his historical account, errantly seeing the rise of a free market in labor with the Poor Law reforms of 1834 when in fact no such freedom existed. Therefore, he could not provide a fully-fledged institutional analysis of economic embeddedness that lies at the core of his theory. To realize a fully-developed institutional analysis I argue that we need to bring class conflict back into the narrative of institutional change through an analysis of legality and its transformation. I partly map out the outlines of a revised institutional analysis that places emphasis on the spatial organization of power, with 'stateness' conceptualized as a variable in which political power (and more especially authority) is scrutinized as historically accreted institutional structures. I also emphasize the historically specific role of the 'local state' in this narrative. ..PAT.-Unpublished Manuscript
Keywords: capitalists & financiers; criminal procedure; industrial laws & legislation; industrial relations; institutional embeddedness; labor laws & legislation; labour laws & legislation; law; quality control

Embeddedness as a Process - Chajewski, Leszek (Conference Papers -- American Sociological Association, 2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (Conference Papers -- American Sociological Association, 2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Keywords: Great Transformation, The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (Conference Papers -- Law & Society, 2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Keywords: DURKHEIM, Emile; WEBER, Max, 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

The World-Historical Origins of Pan-Islamic Nationalism in Iran - Araghi, Farshad (Conference Papers -- American Sociological Association, 2003)
In examining the world-historical context of the rise of pan-Islamic nationalism in Iran, this paper posits Islamic fundamentalism as a modern and global (rather than premodern and local) movement. Drawing on Polanyi and linking economy, polity, and culture, this study traces the origins of pan-Islamic nationalism in Iran to the transformation of the world-market relations in the second half of the nineteenth century and the rise of the food/agrarian regime after 1870. It shows that the relations of the state and the mercantile classes with the world market led to conflicting developments, viz., the national "contraction" of the state on the one hand and the international "expansion" of commercial classes on the other hand. The latter, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European expansion in the "Islamic world." Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for the struggle for the nationalization of the state. Hence, as a historical form, modernity and nationalism in the late nineteenth century Iran took a nonsecular character. Later, the Cold War politics revivified the pan-Islamic component of Iranian nationalism, creating the context for the rise to power of fundamentalism in the 1980s. The paper warns against the reification of place and culture rooted in binary conceptualizations of the local and the global phenomena.
Keywords: Iran; Islam; Islamic fundamentalism; culture; fundamentalism; market; nationalism; pan-Islamism; protestant fundamentalism; religion; religious fundamentalism; world; world-market relations

Labor Organizing and Neoliberal Politics - Rudy, Preston (Conference Papers -- American Sociological Association, 2003)
Neo-liberal policies and practices which impugn state policies as artificial interferences in the smooth operation of markets are at work globally, nationally and locally. Based on research about the Justice for Janitors in California, this paper examines the experience of the campaigns in San Jose and Sacramento. The paper is organized around a tension between two issues about markets that are explained by Karl Polanyi: their social reality as complex political constructions and the ideological justification for disembedding markets, aka the "Liberal Creed". In both campaigns the Justice for Janitors exposed the embeddedness of employers. On the other hand, in the ideological construction of their campaigns, the Justice for Janitors have not clearly confronted the "liberal creed" that justifies neo-liberal market practices. The JfJ campaigns have been successful at creating accountability for employers and politicians by revealing the concrete social relations within which markets are embedded, though they have largely failed to articulate an oppositional ideology to the liberal creed. At a minimum confronting this creed would place the state as central to the construction of market practices. The successes at instituting accountability of employers to democratic communities and the centrality of the state in securing that accountability will be undermined unless JfJ exposes the flaws of the liberal creed and clearly explains the importance of the state in securing the justice they seek.
Keywords: United States; ideology; labor; labour; liberal creed; liberalism; markets; neoliberalism; political planning